Operations Research in the USSR as Education and Research Work - Siroyezhin, Ivan M. (Management Science, 1965)
This paper presents a general discussion of operations research education with special attention to the program of the Department of Mathematical Economics 1 at Leningrad University. The influence of the dual aims of providing students with knowledge and professional skills and developing desirable social objectives on curricular development are traced. Some comparisons between OR educational program in the U.S.S.R. and elsewhere are made. The flavor of the program is somewhat indicated by descriptions of student research projects.